Unfinished business: Thomas Duff of Newry - Casey, Christine (My University, 2020)
The Festschrift is the friend of unfinished research relegated to shelf or drawer, too hard-won and engaging to be forgotten. The date ‘24th April 1985’ is inscribed on a manuscript transcription made at Armagh in a file which has gathered dust for two decades, its subject Thomas Duff of Newry. Though Duff has since been the subject of a student dissertation, a journal article and an entry in the Dictionary of Irish Architects at the Irish Architectural Archive, his work remains under-researched for an architect of such national significance. This short essay in honour of Noel Ross revisits research of the 1980s with the aim of encouraging fresh scholarly interest in Duff’s architecture and its place in the wider context of Gothic Revival architecture in Ireland, a burgeoning field of enquiry in which the iconographic, representative and economic aspects of revivalism are of greater concern than the stylistic and qualitative preoccupations of the 1980s. The shifting sands of historiography are acutely felt in the excavation of decades-old jottings in which tantalising short-hand gaps in transcription point to overlooked material of newly-felt significance. Several themes emerge from these youthful notes not least the business of architecture and building construction, the relationship of architect and client, and the close connections between the neighbouring towns of Dundalk and Newry which fostered emulation in design and craftsmanship, a factor of increasing significance for historians, here illustrated by the fortunes of Saint Patrick’s Pro-Cathedral at Dundalk, Duff’s acknowledged masterpiece, and arguably ‘the most perfect Gothic church of the period in the entire country’.
PUBLISHED
Permission granted by Editor of CLAHS for upload to TARA of proof
Keywords: Making Ireland; Irish History; History